catena-Poly[[aqua(1,10-phenanthroline)cobalt(II)]-μ-4,4′-(propane-1,3-diyldioxy)dibenzoato] - Shen, Su-Mei (International Union of Crystallography, 2009)
In the title compound, [Co(C(17)H(14)O(6))(C(12)H(8)N(2))(H(2)O)](n), the Co(II) atom is coordinated by a monodentate 4,4′-(propane-1,3-diyldioxy)dibenzoate (cpp) dianion, a water molecule and a chelating 1,10-phenanthroline (phen) ligand. A symmetry-generated cpp ligand completes the CoN(2)O(3) trigonal-bipyramidal geometry for the metal ion, with the N atoms occupying both equatorial and axial sites. The bridging cpp ligands form chains propagating in [110] and O—H⋯O hydrogen bonds consolidate the packing.